2018
DOI: 10.1039/c8ra07576j
|View full text |Cite
|
Sign up to set email alerts
|

Advanced palladium free approach to the synthesis of substituted alkene oxindoles via aluminum-promoted Knoevenagel reaction

Abstract: A synthetic route for the synthesis of C24, as well as for the design of focused libraries of direct AMPK activators was developed based on a convergent strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
(29 reference statements)
1
13
0
Order By: Relevance
“…However, we developed a method of condensation, which allows to obtain benzophenone derivatives according to the same scheme. [37] Therefore, we synthesized several new compounds between 3 a and C24 with intermediate activity according to Scheme 1. The lipophilicity of molecule binding fragments was the main varying parameter when changing the structure from 3 a to C24 ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, we developed a method of condensation, which allows to obtain benzophenone derivatives according to the same scheme. [37] Therefore, we synthesized several new compounds between 3 a and C24 with intermediate activity according to Scheme 1. The lipophilicity of molecule binding fragments was the main varying parameter when changing the structure from 3 a to C24 ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The library was based on classes of compounds studied in our laboratory, which in in vitro experiments showed activity comparable to the activity of substances at the stage of clinical trials [18,19] (Fig. 1).…”
Section: Metarials and Methodsmentioning
confidence: 99%
“…1). In the course of work on optimization of MDM2 inhibitors based on indolinones and isoindolinones [19][20][21], we found fragments of the structure that can be modified with minimal risk of a decrease in the target activity, i.e. ability to inhibit the formation of the complex MDM2-p53.…”
Section: Metarials and Methodsmentioning
confidence: 99%
“…Recently, Novikova et al reported a palladium-free approach to the synthesis of YLF466D via aluminum-promoted Knoevenagel reaction. 21 However, the E-and Z-isomers (10 and 11) produced by this method have E/Z ≈ 37/63 (Eisomer is required due to its higher activity toward AMPK) and the separation of these isomers would be challenging.…”
Section: Palladium-catalyzed C−h Activation (Key Intermediate 7)mentioning
confidence: 99%
“…Recently, YLF466D was reported to be prepared through a Lewis acid-promoted Knoevenagel reaction, which gave a mixture of Z-and E-isomers, which was subsequently separated via column chromatography. 21 As the Z-isomer displayed lower activating efficacy toward AMPK, 20 this geometryunselective approach to YLF466D is not an ideal choice for its scale-up synthesis.…”
Section: ■ Introductionmentioning
confidence: 99%